Phenylbutazone concentrations in synovial fluid following administration via intravenous regional limb perfusion in the forelimbs of six adult horses - O’Brien, Molly; Mochel, Jonathan P.; Kersh, Kevin; Wang, Chong; Troy, Jarrod (Frontiers in Veterinary Science, 2023)
Background Pain management is critical to equine welfare with non-steroidal anti-inflammatory drugs (NSAID) commonly used in horses. However, systemic NSAID use is limited by harmful gastrointestinal and renal side effects. Intravenous regional limb perfusion (IVRLP) is a technique used in horses that produces high, local antibiotic concentrations while limiting systemic circulation. NSAID-IVRLP would be a novel method of local pain management while limiting systemic NSAID side effects. To date, NSAID-IVRLP administration has not been reported in horses. This study aimed to identify the pharmacokinetics and local complications associated with using the NSAID phenylbutazone (PBZ) for IVRLP in six standing adult horses. Methods PBZ-IVRLP, at a dose of 2.2 mg/kg PBZ, was performed in a randomly assigned forelimb cephalic vein in 6 standing, healthy adult horses. A placebo-IVRLP was performed in the contralateral forelimb for comparison. Systemic serum and radiocarpal joint synovial fluid PBZ concentrations were identified at various timepoints (before IVRLP T-0 h, just after tourniquet removal T-0.5, 1.5, 3, 5, 12, 16, and 24 h post IVRLP) for non-compartmental pharmacokinetic analysis and concentration over time curves. Local complications associated with PBZ-IVRP were evaluated for up to 7 days following PBZ-IVRLP using physical and ultrasonographic assessment. On day 7 horses were humanely euthanized with histology performed on both forelimbs at PBZ-IVRLP and placebo-IVRLP administration sites. Results Non-compartmental pharmacokinetics for PBZ, and its major metabolite oxyphenbutazone (OBZ), were determined for serum and synovial fluid. Synovial PBZ concentrations (mean ± SD; 1.9 ± 2.1 μg/mL) were significantly lower (p = 0.03; CI,0.46–7.36) than serum PBZ concentrations (5.8 ± 5.1 μg/mL) at any time point. Physical and ultrasonographic measurements were not significantly different between PBZ- and placebo-IVRLP forelimbs. The most common histologic findings included focal deep dermal/subcutaneous hemorrhage and edema. Two horses showed perivasculitis and one horse showed a resolving thrombus in the cephalic vein of the PBZ-IVRLP limb. This horse also had severe perivasculitis and fibrinosuppurative dermatitis/panniculitis in the placebo-IVRLP limb. Conclusion PBZ-IVRLP pharmacokinetics at a 2.2 mg/kg dose showed no benefit compared to systemic PBZ administration in standing adult horses. Local complications associated with PBZ-IVRLP were similar to placebo-IVRLP on physical and ultrasonographic evaluation.